COGNITIVE LINGUISTICS: BASIC APPROACHES AND CONCEPTS IN ENGLISH AND UZBEK LANGUAGES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the formation, development and significance of cognitive linguistics in modern linguistics. The author summarizes the views of English and Uzbek linguists on cognitive linguistics and the stages of its formation. Cognitive linguistics emerged in the 1970s as a protest against formal linguistic approaches. Its basis goes back to the development of cognitive science in the 1960s and 1970s, such as human categorization and gestalt psychology. Although the initial research in this area was carried out by a small number of scientists, in the 1990s the number of cognitive linguists increased, and the Journal of Cognitive Linguistics and the International Society for Cognitive Linguistics were founded. Cognitive linguistics is an approach based on general principles, views and hypotheses, rather than a specific theory. This approach aims to study conceptualization patterns, considering language as a mirror of human thinking. The hypothesis that language reflects the structure and properties of human consciousness forms the methodological basis of this field. The article emphasizes the inextricable link between cognitive linguistics and social, cultural and linguistic processes. This direction is developing in collaboration with various disciplines, including psychology, anthropology, philosophy and computer science, opening up new opportunities for scientific research. Cognitive linguistics is aimed at studying the mechanisms of storing, expressing and transmitting knowledge through language, which is of great importance in studying the grammar of thought of Uzbek speakers. The article shows cognitive linguistics as a product of interdisciplinary dialogue and determines its place in scientific research. This article provides a detailed description of the stages of formation of cognitive linguistics in English and Uzbek linguistics.